ENFERMIDADE CARDIOVASCULAR E PNEUMONIA NÃO ESPECIFICADA: UM ESTUDO DE CASO - Herr, Gerli; Prauchner, Caroline K.; Rosanelli, Cleci P.; Fernandes, Bianca R.; Kuhn, Ohana T.; Scarton, Juliane (Salão do Conhecimento, 2013)
Resumo